Innovative Techniques/Technologies to Enhance the Durability of Civil Infra Structures (PART 1: Corrosion Monitoring Techniques/Technologies) - Thangavel, Kanagamani (Innovations in Corrosion and Materials Science (Discontinued), 2017)
Background: Corrosion monitoring in other words the health checkup of civil infrastructures is an essential survey required for maintaining the service life of concrete structures. In order to avoid the catastrophic failures, corrosion monitoring and effective additional protective measures must be undertaken at the initial stage itself. The in situ corrosion monitoring techniques provide information on the state of condition of reinforcement rods and concrete. For concrete, concrete resistivity measurements, and in situ strength by ultrasonic pulse velocity measurements are discussed. For embedded steel, techniques (i) for identifying corrosion pits and cracks by acoustic emission (ii) for identifying grouted and non-grouted portions of pre stressed steel by radiography (iii) corrosion rate of embedded steel by linear polarization resistance and potentiostatic pulse technique are discussed. Cyclic polarization and potentio dynamic polarization tests were conducted to characterize and evaluate MnO2 sensors. The half-cell potential of MnO2 in concrete is found to be +200 mV Vs SCE. The potential of embedded steel with reference to MnO2 are -315 mV and -525 mV for non-corroding and corroding conditions of embedded steel in concrete. Rebar potential sensors and corrosion rate monitoring probe sensors were embedded in real concrete structures for long-term corrosion monitoring studies. The sensor materials provide information on the corrosion condition of embedded steel during the service life of structures. Corrosion monitoring techniques identify the corrosion hot spot areas; so that repairs and rehabilitation work can be carried out at the right time before substantial damage / collapse occurs in the existing concrete bridges. Methods: The corrosion condition assessment of any civil infrastructures such as marine bridges, double wall concrete nuclear reactors and multi storey buildings, on-shore and offshore concrete structures will be implemented using advanced corrosion monitoring portable equipments. Results: The in situ concrete parameters such as compressive strength obtained from Rebound Hammer test and Ultrasonic Pulse velocity measurements were compared and analyzed for service life prediction. The potential of embedded steel in concrete and corrosion rate of embedded steel in concrete are the key parameters for determining the residual life of concrete structures. The corrosion currents measured from various electro chemical techniques were converted into millimeter per year (mmpy) units and correlated with service life of civil structures. Conclusion: The rebar potential measurements indicate whether the embedded steel exists in the passive or active conditions. The corrosion rate of embedded steel indicates the loss of diameter due to corrosion process. Based on the data collected, the site investigated will be classified as severely corroded and moderately corroded areas. The severely corroded areas will be identified and recommended for repair and rehabilitation to be implemented to enhance the durability of the civil infrastructures.
Keywords: radiography